CSR disclosure in the context of resource-based view theory / Suzana San and Nor Jana Salim - San, Suzana; Salim, Nor Jana (2013)
Resource-Based View (RBV) theory which identifies the nature of company’s resources such as valuable, rare, imperfectly imitable and non-substitutable makes contribution to CSR disclosure. The purpose of this study is to examine the relationship of investment and CEO international experience with CSR disclosure. As a proxy to CSR disclosure the words count is analyzed from the annual report of Malaysian PLCs in sensitive industries from 2007 to 2009. The finding reveals that only investment is significant at 1% level to influence CSR disclosure positively, while CEO international experience was not proven to have influence on CSR disclosure. This study supports the dimensions of CSR disclosure analysis using RBV theory especially in Malaysia context after it is made mandatory to PLCs.